Implementasi Mobile Application E-Ticketing Pariwisata Planetarium Jagad Raya Tenggarong - Rizky Martha Sutama; Yulindawati Yulindawati; Ivan Haristyawan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2026)
Planetarium Jagad Raya Tenggarong is one of the educational tourism destinations in Kutai Kartanegara that offers astronomy-based learning experiences for students, families, and the general public. However, the existing ticket reservation process is still conducted manually, causing long queues, inefficient data management, and limited access to information regarding show schedules and ticket availability. This study aims to design and implement a mobile-based e-ticketing application to improve the efficiency and quality of ticket reservation services. The system was developed using the Waterfall software development method, which consists of requirements analysis, system design, implementation, testing, and deployment. The application provides several key features, including user registration, online ticket booking, digital payment integration, electronic ticket generation, and access to updated show schedules. System functionality was evaluated using Black Box Testing to verify that each feature operates according to the specified requirements, while Beta Testing was conducted to measure user satisfaction and application usability. The testing results demonstrate that all system functions operate successfully and meet user expectations. Users also reported positive responses regarding the application's ease of use, accessibility, and efficiency. The implementation of the mobile-based e-ticketing application effectively simplifies the ticket purchasing process, reduces waiting time, minimizes manual administrative tasks, and enhances the overall visitor experience, making it a practical digital solution for supporting educational tourism services at Planetarium Jagad Raya Tenggarong.